PENCIPTAAN BUKU ILUSTRASI JAJAN TRADISIONAL DI SURABAYA UNTUK ANAK-ANAK SEBAGAI UPAYA PENGENALAN WARISAN KULINER INDONESIA - Putri, Rizki Ardiyanti; Fianto, Achmad Yanu Alif; Riyanto, Darwin Yuwono (Jurnal Art Nouveau, 2015)
Abstract : Indonesia has a wide variety of cultures, customs, languages and not to mention food or culinary. Traditional snack is a kind of typical food that comes from every region in Indonesia, and processed in a simple way as well as materials that are easily obtainable. These snacks being sold in traditional markets, therefore this kind of snack is also known as traditional snacks. Snack traditionally been less popular as compared to junk food in every shopping center. In the middle of Surabaya heterogeneous society, snack market seems to begin excluded. People of Surabaya has rarely willing to eat a traditional snack. They prefer to enjoy foods of foreign products. With the emergence of many cafÃ©s, restaurants, and fast food franchise, the snacks that come from the outside like a pastry, too rose prestige because these snacks are considered more prestigious than traditional snack. From the above problems, we need a media that can provide a complete knowledge and information about traditional snacks for Indonesias young generation that can be enjoyed as one of the cultural preservation efforts in order not to be forgotten. The media chosen by the author is the book illustrations. To support the process of delivering a message to the target audience, then the verbal elements used on each page of the book.Â Keywords : Illustration Book, Traditional Snacks, Surabaya Snack, Children.